1995
DOI: 10.1017/s0143385700009792
|View full text |Cite
|
Sign up to set email alerts
|

The flat-trace asymptotics of a uniform system of contractions

Abstract: We develop a variant of the Taylor approximation approach to the periodic points of systems of contraction mappings [Rl] that does not invoke compactness conditions. Our presentation is simpler, in that certain steps are bypassed and only one basic estimate is used (Lemma 1). We also study the distribution of the discrete spectrum for the relevant transfer operators (Proposition 2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…-To study spectral properties of Perron-Frobenius operators (and Ruelle transfer operators, more generally), it is primarily important to find appropriate spaces for them to act on. For C r expanding dynamical systems (r > 1) and C r−1 weights, Ruelle [13], and later Fried [5] and Gundlach-Latushkin [8], showed that the Banach space of C r−1 functions worked nicely. For Anosov diffeomorphisms usual function spaces do not work.…”
Section: Spectral Stabilitymentioning
confidence: 99%
“…-To study spectral properties of Perron-Frobenius operators (and Ruelle transfer operators, more generally), it is primarily important to find appropriate spaces for them to act on. For C r expanding dynamical systems (r > 1) and C r−1 weights, Ruelle [13], and later Fried [5] and Gundlach-Latushkin [8], showed that the Banach space of C r−1 functions worked nicely. For Anosov diffeomorphisms usual function spaces do not work.…”
Section: Spectral Stabilitymentioning
confidence: 99%
“…Gallavotti (1976) then found a differentiable Axiom A flow whose Ruelle dynamical zeta function ζ(s) had a non-polar singularity. Much more recently Fried (1995b) proved, combining Grothendieck techniques from the pioneering article of Ruelle (1976b) with novel ideas of Rugh (1994), that the dynamical zeta function of a real analytic Axiom A flow (without assuming smoothness of the stable and unstable bundles) could indeed be extended meromorphically to C (see Theorem 4.1 later).…”
Section: Introductionmentioning
confidence: 99%
“…Let A be a transfer operator in C(X ) and let A * : C * (X ) → C * (X ) be the adjoint operator to A. The formulae (28) and (29) can be rewritten in the following way:…”
Section: A B Antonevich Et Almentioning
confidence: 99%